PENGGUNAAN MINYAK JELANTAH SEBAGAI FAKTOR RISIKO HIPERTENSI DI KABUPATEN BANYUMAS - , HENRIETTA IMELDA TONDONG ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Hypertension is a non communicable disease with the highest number of cases at District of Banyumas. The prevalence of hypertension at District of Kebumen is 39.2%, highest at the Province of Jawa Tengah. Reuse of cooking oil has become cultural part of the Indonesian community in relation to the habit of consuming fried foods. Banyumas district community has the habit of consuming fried foods. Objective: To find out risk factor of hypertension in people that reused cooking oil and assess the risk of reuse of cooking oil at District of Banyumas. Method: The study was analytic observational with case control design through matching of age and gender. Samples consisted of 308 people, 154 as cases (those visiting health center and diagnosed hypertensive) and 154 as control.(those visiting health center and not hypertensive). Results: The result of bivariate analysis showed that re-use of cooking oil was risk factor with score of OR=4.800 (CI 95%=2.958-7.789), and p=0.000, intake of sodium OR=3.635 (CI 95%=2.271-5.819), and p=0.000, obesity OR=2.127 (CI 95%=1.342-3.373), and p=0.001, and physical activity OR=3.430 (CI 95%=2.148-5.478), and p=0.000. The result of multivariate analysis showed reuse of cooking oil was the most dominant factor for the prevalence of hypertension at District of Banyumas with score of OR=4.003 (CI 95%=2.100-9.102), and sig=0.001. Conclusion: Reuse of cooking oil will increase the risk of incident hypertension, and is the most dominant risk factor for the incident of hypertension at District of Banyumas.